2011
DOI: 10.1021/nn202493w
|View full text |Cite
|
Sign up to set email alerts
|

Using Polymer Conformation to Control Architecture in Semiconducting Polymer/Viral Capsid Assemblies

Abstract: Cowpea Chlorotic Mottle Virus is a single-stranded RNA plant virus with a diameter of 28 nm. The proteins comprising the capsid of this virus can be purified and reassembled either by themselves to form hollow structures, or with polyanions like double-stranded DNA or single-stranded RNA. Depending on pH and ionic strength, a diverse range of structures and shapes can form. The work presented here focuses on using these proteins to encapsulate a fluorescent polyanionic semiconducting polymer, MPS-PPV (poly-2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 53 publications
0
30
0
Order By: Relevance
“…Bare MPS-PPV chains coiled and formed face-to-face π -stacking among phenyl rings. 28 Therefore, the fluorescence is highly quenched. Once CD-PEI is introduced in the FSNPs, they form a complex with MPS-PPV polymer chains electrostatically, separating and uncoiling individual polymer chains.…”
Section: Resultsmentioning
confidence: 99%
“…Bare MPS-PPV chains coiled and formed face-to-face π -stacking among phenyl rings. 28 Therefore, the fluorescence is highly quenched. Once CD-PEI is introduced in the FSNPs, they form a complex with MPS-PPV polymer chains electrostatically, separating and uncoiling individual polymer chains.…”
Section: Resultsmentioning
confidence: 99%
“…At a low ionic strength, the semi-rigid rod MPS-PPV exhibited a more extended conformation and the VCPs encapsulated the stretched polymer forming a rod-like structure. 79 Brasch and Cornelissen also showed that longer conjugated MPS-PPV chains could not be accommodated into a single VLP. As a result, a cluster of more than two T = 1 VLPs was formed.…”
Section: In Vitro Self-assembly Of Vcpsmentioning
confidence: 99%
“…For example, optically active semiconducting polymer poly-2-methoxy-5-propyloxy sulfonate phenylene vinylene (MPS-PPV) was encapsulated in order to obtain optically active VLPs. 79 This self-assembly route was particularly interesting because two distinct, optically active structures could be created depending on the ionic strength ( Fig. 4b and c).…”
Section: In Vitro Self-assembly Of Vcpsmentioning
confidence: 99%
“…By controlling the polymer conformation using different ionic strengths, going from low to high ionic strength, the morphology changed from rod-like to mixed rod-like/globular to finally completely globular. Additionally, the fluorescent properties also changed with the polymer conformation obtaining not only different overall particle morphologies, but also with different optical and electronic properties [39]. Future research will produce more of these biohybrid materials since new morphologies with new applications will emerge and the strength of combining electrostatic interactions with synthetic and biological structures is a straightforward and easy way of fabrication and allows also for large-scale fabrication under mild aqueous conditions.…”
Section: Artificial Assembly Of Virus Particlesmentioning
confidence: 99%